Transnationell kooperation : en studie av DLA Agro - Eserup, Niclas; Johansson, Oscar (SLU/Dept. of Economics, 2011)
Farmers Cooperative has in recent years developed from national markets to cross-border, international, collaborations. One example is the merger between the Swedish dairy company Arla and Danish MD Foods, where the companies collectively are sought to reduce transaction costs and thus improve efficiency. The Swedish market for commodities (fertilizers and pesticides) in agriculture has for many years been dominated by a few large players, with little opportunity for grain associations and local grain companies to offer their customers a varied range of commodities with a competitive pricing.